Experimental Mathematics. Volume 17, Number 2, 2008 - A K Peters (A K Peters, 2009)
The Homotopy Lie Algebra of a Complex Hyperplane Arrangement Is Not Necessarily Finitely Presented Full TextPDF (316.4 KB) Author Jan-Erik Roos 129-143 No access to content Euclid Prime Sequences over Unique Factorization Domains Full TextPDF (220.2 KB) Authors Nobushige Kurokawa and Takakazu Satoh 145-152 No access to content Decomposition and Enumeration of Triangulated Surfaces Full TextPDF (314.5 KB) Author Gennaro Amendola 153-166 No access to content The Rational Homology Group of Out(Fn) for n ≤ 6 Full TextPDF (2.1 MB) Author Ryo Ohashi 167-179 No access to content Deciding Existence of Rational Points on Curves: An Experiment Full TextPDF (242.7 KB) Authors Nils Bruin and Michael Stoll 181-189 No access to content Confluence of Swallowtail Singularities of the Hyperbolic Schwarz Map Defined by the Hypergeometric Differential Equation Full TextPDF (1.1 MB) Authors Masayuki Noro, Takeshi Sasaki, Kotaro Yamada and Masaaki Yoshida 191-204 No access to content Exploring the Space of Embedded Minimal Surfaces of Finite Total Curvature Full TextPDF (1.0 MB) Author Martin Traizet 205-221 No access to content A Proof of a Recurrence for Bessel Moments Full TextPDF (207.5 KB) Authors Jonathan M. Borwein and Bruno Salvy 223-230 No access to content The Distribution of the Largest Nontrivial Eigenvalues in Families of Random Regular Graphs Full TextPDF (662.8 KB) Authors Steven J. Miller, Tim Novikoff and Anthony Sabelli 231-244 No access to content Nuclear Elements of Degree 6 in the Free Alternative Algebra Full TextPDF (227.5 KB) Authors I. R. Hentzel and L. A. Peresi